PEMODELAN HYBRID POWER SYSTEM UNTUK SISTEM KELISTRIKAN DI KABUPATEN SUMBAWA - , SUMARTONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Energy resources are natural resources strategic valuable and very important to supporting the region development activities in particular sectors of the economy. Energy management which includes the supply, utilization and enterprise shall be done justice, sustainability and so can give optimum benefit for the greater welfare of the people. The use of fossil fuels as a source of electrical energy (PLTD) will cause environmental and technical problems result of pollution and the limited amount of fossil energy reserves. Sumbawa district has a variety of potential sources of renewable energy that can be harnessed to meet the electrical energy needs of society which tends to increase every year such as